The Relationship between Stress and Preclinical Dental Students’ Performance: A Longitudinal Study - Diva Lugassy; Gil Ben-Izhack; Sara Zissu; Rotem Shitrit Lahav; Ophir Rosner; Nir Uziel; Sarit Naishlos; Asaf Shely (International Journal of Dentistry)
Background. The aim of this study was to evaluate the changing levels of stress among dental students during 8 months of a basic manual skills course in the preclinical year and to examine the association between stress and dental performance. Methods. A longitudinal study was conducted in the 2023 academic year in a total of 58 (male = 17 and female = 41; mean age = 26.43, range 22–33) undergraduate dental students at Tel Aviv University of dentistry during their fourth year of study. Depression Anxiety Stress Scale (DASS-21) and Dental Environment Stress (DES) questionnaires were used to assess the psychological well-being and the severity of DASS symptoms experienced by the students. The students’ dental performances were assessed using two manual tests on plastic teeth. The questionnaires and the manual tests were used at three periods of time, T0, T1, and T2. Wilcoxon signed-rank tests were performed to compare the DASS scores and DES stressors of dental students between T0, T1, and T2. Kendall’s nonparametric correlations were calculated to investigate the relationships of DES stressors and depression, anxiety, and stress scores with manual performance. Conclusions. The perception of high stress by dental students is due to the stressful education process of the preclinical year. There is an inverse correlation between the lower level of anxiety and the increase level of dental performance with 74% of the variance in dental performance explained by the anxiety score. Work-related stressors such as manual skills might reduce dental performance in contrast to non-work-related factors such as financial obligations, personal issues, and family factors, which might increase student dental performance.